Factors Influencing the Application of Accounting Systems Among Small to Medium Enterprises (SMEs) in Kurdistan - Rebin Bilal Mohammed; Sardar Jalal Braim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The study identifies and analyses factors influencing the application of accounting systems among SMEs to find ways of improving the adoption of accounting systems matching the situational context and needs of SMEs. 196 responses collected from SMEs in Erbil, Kurdistan were analyzed using multiple regression to ascertain the relationship and magnitude of effects posed by identified five factors on the application of accounting systems. The results showed that perceived business activities, accounting systems perceived ease of use, accounting systems reporting features, and accounting systems security features had positive effects on the application of accounting systems. Accounting systems costs had insignificant effects on the application of accounting systems. It was suggested that accounting systems developers must develop accounting programs that are easy to use and are specifically designed to cater for the needs of SMEs. Additionally, SMEs were encouraged to apply cost minimization and revenue maximization strategies to guard against the increase in costs posed by accounting systems acquisition, installation, and maintenance costs.